FUNGSI PEMERINTAH KOTA KUPANG DALAM PENATAAN PEDAGANG KAKI LIMA - Matau, Charol Primus; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
This research was motivated by the non-realization of Government Regulation Number 34 of 2006 concerning Roads. The existence of these street vendors causes various problems. Thus, the government started to regulate street vendors based on Government Regulation Number 34 of 2006. The formulation of the problem in this research is the function of the Kupang City Government in managing street vendors in terms of Government Regulation Number 34 of 2006 concerning roads on El Tari Road, Kupang. This research was conducted in Kupang City. The data sources in this research are both primary and secondary, which are then analyzed using qualitative descriptive analysis. This research shows that the arrangement of street vendors based on Government Regulation Number 34 of 2006 concerning Roads has yet to be fully implemented by the government. In terms of regulation, the government has implemented regional regulations. However, many traders still need to comply with the regulations due to the need for government action to regulate street vendors.